HUBUNGAN KOORDINASI MATA-KAKI DAN KECEPATAN REAKSI DENGAN KETERAMPILAN SEPAK SILA PADA EKSTRAKURIKULER SEPAKTAKRAW SMPN 03 BANTAN - Nurariadi, Nurariadi; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of the research was to get the correlation of ankle coordination and reaction speed with the ability of precepts kick on sepaktakraw extracurricular of SMPN 03 Bantan. The forms of this research was the correlation study, the population in this study was sepaktakraw extracurricular of SMPN 03 Bantan and the sample in this study was 6 students. While the sample tecnique used is total sampling (saturated sample), where all the population as the sample. So, the sample in this study amounted to 6 students. After that, the data is processed with statistics, normality test with liliefors test and correlation at significant level Î± (0,05). The first analysis in the calculation of the correlation between X1 and Y, where rtable at significant level Î± (0,05) = 0,878 means rresult (0,928) > (0,878), which means the hypothesis is accepted and there is a meaningful correlation with a very strong interpretation between ankle coordination with the ability of precepts kick on students sepaktakraw extracurricular SMPN 03 Bantan, a second analysis of in the calculation of the correlation between X2 and Y, where rtable at significant level Î± (0,05) = 0,878 means rresult (0,920) > (0,878), which means the hypothesis is accepted and there is a meaningful correlation with a very strong interpretation between reaction speed with the ability of precepts kick on students sepaktakraw extracurricular SMPN 03 Bantan. The analysis of the three correlation X1 and X2 with Y was obtained, which rtable at significant level Î± (0,05) = 0,878, means Rresult (0,988) > rtable (0,878). Than it can be concluded that the correlation between X1 and X2 with Y or the correlation between ankle coordination with the ability of precepts kick on sepaktakraw extracurricular SMPN 03 Bantan are significant.Keywords : Ankle Coordination, Reaction Speed dan Precepts Kick.